UPAYA POLDA KALIMANTAN BARAT DALAM MENERAPKAN PERATURAN PEMERINTAH NOMOR 2 TAHUN 2003 TENTANG PERATURAN DISIPLIN BAGI ANGGOTA POLRI GUNA MEWUJUDKAN GOOD GOVERNANCE DAN CLEAN GOVERNMENT DI INTERNAL POLRI - ROBERT MARIHOTTUA DAMANIK, SH A.2021141063, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses West Kalimantan Regional Police Efforts in Implementing the Government Regulation No. 2 of 2003 on the Police Disciplinary Regulations for Members To Achieve Good Governance and Clean Government In Polri.Dari Internal research results of this thesis can be concluded that the factors that influence the adoption of Government Regulation No. 2 2003 About the disciplinary Code for members of the Police in the perspective of good governance and clean government is the internal factor of the national police that the legislation on the implementation of the law enforcement discipline INP still there is a regulation that is not clearly and unambiguously, multi interpretation giving rise to legal uncertainty and justice, as a result of law are relatively often subjective, there are still among Leaders unit as Ankum that have not fully give attention on the implementation of the law enforcement duties discipline police members including the officers Provos Police, the level of understanding and application of the rule of law by Penyildik Provos Police in the investigation of the case breach of discipline is still low, the level of discipline, awareness and compliance with national Police on disciplinary rules are binding and apply to her still relatively low so that breaches of discipline remains the case, there are still a lot of intervention, the intervention of the police official in the implementation of the law enforcement discipline of members of the police so that the results of law enforcement is achieved is still relatively subjective and disciplinary law enforcement police members often seem less transparent. While external factors is the slow pace of economic recovery the government resulted in the welfare of members of the police have not been felt, triggering the growth of legal action against the law members of the police, there are legislators who skeptif and vocal voiced about the inability of the police in carrying out their duties as law enforcement, maintainer Kamtibmas and protector and public servants, for their political interests ride with, their efforts certain government agencies on behalf of the interests of the community to put the police institution under a particular department, there are still many negative views of the national police of the state officials, political elite, public officials and the public so that the response to the National Police also negative although the pace of reform has been carried out by organizations Police Still the of interference from state officials, political elite towards the implementation of police duties affect law enforcement discipline of members of the Police, the agency Kompolnas yet fully functioning properly because of product performance is merely giving advice to the president about the main tasks, functions and the role of the police, there are NGOs who are skeptical of the implementation of police duties especially in law enforcement, the level of public trust in the police is low fear of dealing with the police, as a result of the perception of the past where police in facing community to further highlight the violence that is ultimately less concerned for supervising and reluctant to complain about negative action members of the police, even if a complaint but reluctant to testify so that the difficulties in conducting the investigation and utilization of mass media in disseminating information overload and cornering still there is corruption in the body PolriUpaya to do West Kalimantan Regional Police in Law Enforcement Discipline Share Police members in the perspective of good governance and clean government is doing Renewal Regulations Police Professional Code of conduct; Confirming Gait Propam Police As Garda Leading Member2Discipline Law Enforcement Police; Breeding Police Profession, Professional Commitment Implementation and Institutional Revitalization Police.Keywords: Role of the Indonesian Armed Forces, In Security, the Frontier Army.ABSTRAKTesis ini membahas Upaya Polda Kalimantan Barat Dalam Menerapkan Peraturan Pemerintah Nomor 2 Tahun 2003 Tentang Peraturan Disiplin Bagi Anggota Polri Guna Mewujudkan Good Governance Dan Clean Government Di Internal Polri.Dari hasil penelitian tesis ini diperoleh kesimpulan Bahwa faktor-faktor yang mempengaruhi Penerapan Peraturan Pemerintah Nomor 2 Tahun 2003 Tentang Peraturan Disiplin Bagi Anggota Polri dalam perspektif good governance & clean government adalah Faktor Internal polri yaitu pada peraturan perundang-undangan tentang pelaksanaan penegakan hukum disiplin Anggota Polri masih ada aturan hukumnya yang tidak jelas dan tegas, multi tafsir sehingga menimbulkan ketidak pastian hukum dan keadilan, akibatnya penerapan hukumnya relatif sering bersifat subyektif, masih ada di antara Pimpinan satuan selaku Ankum yang belum sepenuhnya memberikan atensi atas pelaksanaan tugas penegakan hukum disiplin anggota Polri termasuk kepada petugas Provos Polri, tingkat pemahaman dan penerapan aturan hukum oleh Penyildik Provos Polri dalam penyidikan perkara pelanggaran disiplin masih rendah, tingkat disiplin, kesadaran dan kepatuhan Anggota Polri atas peraturan disiplin yang mengikat dan berlaku baginya masih relatif rendah sehingga pelanggaran disiplin tetap terjadi, masih banyak campur tangan, intervensi dari Para pejabat Polri dalam pelaksanaan penegakan hukum disiplin anggota Polri sehingga hasil dari penegakan hukum yang dicapai masih relatif subyektif dan penegakan hukum disiplin anggota Polri sering terkesan kurang transparan. Sedangkan faktor eksternal yaitu lambannya pemulihan ekonomi pemerintah berakibat kesejahteraan anggota Polri belum dirasakan, memicu tumbuhnya tindakan hukum melanggar hukum anggota Polri, masih ada anggota legislatif yang skeptif dan vocal menyuarakan tentang ketidakmampuan Polri dalam melaksanakan tugasnya sebagai penegak hukum, pemelihara Kamtibmas serta pelindung, pengayom dan pelayan masyarakat, karena adanya kepentingan politik yang memboncengi, adanya usaha instansi pemerintah tertentu yang mengatasnamakan kepentingan masyarakat untuk menempatkan institusi Polri dibawah suatu departemen tertentu, masih banyak pandangan negatif terhadap polri dari pejabat negara, elit politik, pejabat publik maupun masyarakat sehingga respon kepada Polri juga negatif walaupun langkah reformasi telah dilakukan oleh organisasi Polri, Masih adanya interpensi pejabat negara, elit politik terhadap pelaksanaan tugas Polri mempengaruhi penegak hukum disiplin anggota Polri, lembaga Kompolnas belum sepenuhnya berfungsi dengan baik karena produk kinerjanya baru sebatas pemberian saran kepada Presiden tentang tugas pokok, fungsi dan peranan Polri, masih ada LSM yang bersifat skeptic atas pelaksanaan tugas Polri khusunya dalam penegakan hukum, tingkat kepercayaan masyarakat terhadap Polri masih rendah takut berurusan dengan Polri, sebagai akibat persepsi masa lampau dimana Polri dalam mengahadapi masyarakat lebih menonjolkan kekerasan yang pada akhirnya kurang peduli untuk melakukan pengawasan dan enggan mengadukan tindakan negatif anggota Polri, kalaupun mengadukan akan tetapi enggan memberikan kesaksian sehingga kesulitan dalam melakukan penyidikannya dan Pemanfaatan media masa dalam menyebarluaskan informasi yang berlebihan dan menyudutkan masih adanya KKN dalam tubuh PolriUpaya yang harus dilakukan Polda Kalimantan Barat Dalam Penegakan Hukum Disiplin Bagi Anggota Polri dalam perspektif good governance & clean government adalah dengan melakukan Pembaharuan Peraturan Kode Etik Profesi Polri; Memantapkan Kiprah Propam Polri Sebagai Garda Terdepan Penegakan Hukum Disiplin Anggota Polri; Pemuliaan Profesi Polri, Implementasi Komitmen Profesi, dan Revitalisasi Institusi Polri.Keywords: Efforts Police, In Realize, Good Governance, Clean Government.